2019
DOI: 10.1186/s12909-019-1692-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and evaluating an e-portfolio for postgraduate family medicine training in the Western Cape, South Africa

Abstract: Background In South Africa it is compulsory to submit a satisfactory portfolio of learning to gain entrance to the national exit examination of the College of Family Physicians and to qualify as a family physician. A paper-based portfolio has been implemented thus far and the need for an electronic portfolio (e-portfolio) was identified. The aim of the study was to describe and evaluate the implementation of an e-portfolio for the training of family medicine registrars in the Western Cape province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
0
30
0
4
Order By: Relevance
“…Similarly, another study conducted in South Africa revealed that EP is more user-friendly and less cumbersome. [25] Participants argue that PBP involves more financial cost than EP due to the large amount of paper to be printed. Most participants considered EP less expensive than PBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another study conducted in South Africa revealed that EP is more user-friendly and less cumbersome. [25] Participants argue that PBP involves more financial cost than EP due to the large amount of paper to be printed. Most participants considered EP less expensive than PBP.…”
Section: Discussionmentioning
confidence: 99%
“…The study done by Buzzetto-More [26] reported that students spent more time on PBP. As in the study done by [25] students spend more time binding the papers and experience anxiety about losing those papers.…”
Section: Discussionmentioning
confidence: 99%
“…O portfólio é um instrumento de avaliação que evidencia a aprendizagem significativa, porque inscreve-se no contexto de uma avaliação formativa pautada no feedback, possibilita a autoavaliação do estudante sobre seu processo ensino-aprendizagem e en- fatiza o seu potencial reflexivo e crítico. A utilização do portfólio on-line potencializou o ambiente de ensino e as formas de aprendizagem 10,11 dos estudantes foram analisadas a partir dos dados disponibilizados pelo moodle, o que possibilitou melhorias não só nos critérios de avaliação como também no roteiro de perguntas do portfólio.…”
Section: Discussionunclassified
“…It is the golden exam in most of the postgraduate degrees. 25,26 Adding another important point to the fairness and objectivity of the exam, the study suggested the use of a standardized setting as the national license exam is considered to be highstakes one. The criterion-referenced standard is preferred for theoretical and clinical parts of the exam.…”
Section: Discussionmentioning
confidence: 99%